Breve til Marie Toft fra 1840'erne - Holm, Jette (Grundtvig-Studier, 2018)
Letters to Marie Toft from the 1840es Letters exchanged between Grundtvig and Marie Toft, his second wife, have been destroyed, except for one letter that Toft wrote to Grundtvig in 1847 and an unfinished, unsent one he wrote to her in 1848. Grundtvig’s letter is transcribed here together with seven others to Marie Toft, from P.A. Fenger, J.F. Fenger and J.G. Willemoes, which collectively shed light on Marie Toft’s thinking in the early 1840s, when a religious revival was taking place in Western Zealand. The letters show Toft becoming involved in the movement and, later, increasingly attracted to Grundtvig and his theology.